Executing innovation : expert solutions to everyday challenges. (Pocket mentor series., 2009)
"Ideas are not enough: successful innovation requires real-life execution from start to finish. This book helps you move your initiatives forward by showing you how to: Develop a motivating vision statement; Identify stakeholders and build a strong business case; Overcome explicit and hidden resistance to change; and Maintain the momentum around your project."--BOOK JACKET.